1996
DOI: 10.3109/09513599609012314
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of receptors for insulin-like growth factor type I on cultured human endometrial stromal cells: downregulation by progesterone

Abstract: Because insulin-like growth factor type I (IGF-I) is reputed to be involved in the endometrial decidualization, we analyzed the expression of IGF-I receptors in an in vitro system of human endometrial stromal cells. Competitive binding studies of both intact stromal cells and membrane preparation indicated the presence of specific components with high affinity for binding IGF-I. Half-maximum displacement was obtained with 2.3 nmol/l native IGF-I, whereas insulin was unable to achieve half-maximum displacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We have here extended these data to show the distribution of the protein through the normal cycle and, most importantly, its expression in mid secretory luminal epithelium. Direct evidence for hormonal control of IGF1R expression comes from studies in isolated human endometrial cells that report IGF1R downregulation by progesterone (Strowitzki et al, 1996). In rats, IGF1R expression in the uterus is enhanced by estrogen treatment (Ghahary and Murphy, 1989) and in baboons, expression at the glandular and luminal epithelium undergoes cyclic changes and is upregulated by estrogen (Hild-Petito et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…We have here extended these data to show the distribution of the protein through the normal cycle and, most importantly, its expression in mid secretory luminal epithelium. Direct evidence for hormonal control of IGF1R expression comes from studies in isolated human endometrial cells that report IGF1R downregulation by progesterone (Strowitzki et al, 1996). In rats, IGF1R expression in the uterus is enhanced by estrogen treatment (Ghahary and Murphy, 1989) and in baboons, expression at the glandular and luminal epithelium undergoes cyclic changes and is upregulated by estrogen (Hild-Petito et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…IGF-IR is localized to the luminal and glandular epithelium as well as the stroma, and its expression is down-regulated by progesterone (19,20). In endometrial cells, the activity of the phosphoinositide-3-kinase/Akt pathway is also critically regulated by the activity of phosphatase and tensin homologue deleted on chromosome 10 (PTEN), a lipid phosphatase that negatively regulates phosphoinositide-3-kinase activity by the dephosphorylation of phosphoinositol (3,4,5) triphosphate (21).…”
mentioning
confidence: 99%
“…IGF-1 activity is altered during the menstrual cycle. Strowitzki et al (7) demonstrated that the number of IGF-1 receptors is not cycle de- (10,11). In summary, the results of this study suggest that IGF-BP could modulate the action of IGF-1 throughout the menstrual cycle, and its higher concentration in the progestogenic phase may play a role in the implantation process.…”
Section: Discussionmentioning
confidence: 47%